2023
DOI: 10.1039/d3nj00355h
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally, non-peripherally and axially pyrazoline-fused phthalocyanines: synthesis, aggregation behaviour, fluorescence, singlet oxygen generation, and photodegradation studies

Abstract: Pyrazoline-fused peripheral zinc phthalocyanine (HY-ZnPcP) showed the highest singlet oxygen generation in DMSO, and it is thought to be a photosensitizer candidate for photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The authors suggested that, the HY-ZnPcp molecule, Φ Δ 0.73%, which produced the most singlet oxygen among the three produced phthalocyanines (HY-ZnPcp, HY-ZnPcnp, and HY-SiPc), could be regarded as a photosensitizer candidate for PDT. 149…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%
“…The authors suggested that, the HY-ZnPcp molecule, Φ Δ 0.73%, which produced the most singlet oxygen among the three produced phthalocyanines (HY-ZnPcp, HY-ZnPcnp, and HY-SiPc), could be regarded as a photosensitizer candidate for PDT. 149…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%
“…The highly effective reactivity of singlet oxygen can cause severe damage to biological systems such as DNA and RNA, resulting in cell death. When enough singlet oxygen is produced during the energy transfer from the photosensitizer to the oxygen molecule, effective cell death can be obtained [ 49 ].…”
Section: Photophysical and Photochemical Studies Of Water-soluble Pht...mentioning
confidence: 99%